2001
DOI: 10.1209/epl/i2001-00260-6
|View full text |Cite
|
Sign up to set email alerts
|

Competition and multiscaling in evolving networks

Abstract: The rate at which nodes in a network increase their connectivity depends on their fitness to compete for links. For example, in social networks some individuals acquire more social links than others, or on the www some webpages attract considerably more links than others. We find that this competition for links translates into multiscaling, i.e. a fitness dependent dynamic exponent, allowing fitter nodes to overcome the more connected but less fit ones. Uncovering this fitter-gets-richer phenomena can help us … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
828
4
26

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 877 publications
(892 citation statements)
references
References 20 publications
17
828
4
26
Order By: Relevance
“…The factor m is related to the fact that one new node contributes with m links to the network and the sum in the denominator is over all pre-existed nodes. The solution to equation 3 is given by [4]:…”
Section: Model and Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…The factor m is related to the fact that one new node contributes with m links to the network and the sum in the denominator is over all pre-existed nodes. The solution to equation 3 is given by [4]:…”
Section: Model and Theorymentioning
confidence: 99%
“…However such a model cannot to describe the topological properties of real complex networks due to some physic quantities them associated by usual exponential laws instead of power-law asymptotic behavior. Furthermore, in general real networks are more complex than Erdös and Rényi model and exhibit birth and death of nodes, aging [2], the links depending on some parameter (connectivity [3], fitness [4,5], geographic distance [6,7], etc).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The influencers became the hubs and affected many of those involved. Hence, in this work we consider a voting model in terms of different kinds of graphs, namely random graphs, the Barabási-Albert(BA) model [18], and the fitness model [19], [20], and compare the results to determine the effect of networks.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that the BA and MM model have no disassortativity [27,28]. Pastor-Satorras et al [28] and Barrat et al [31] respectively argue that disassortativity emerges with competitive dynamics [32] and weight-driven dynamics [33], suggesting that growing mechanism needs to include fitness such as spatial distance [34], aging [35], and so on.…”
Section: Introductionmentioning
confidence: 99%